Efektifitas Penerapan Asas Kontradiktur Delimitasi pada Layanan Pertanahan di Kantor Pertanahan Kota Gorontalo - Maidon C. Musdram; Sastro M. Wantu; Yanti Aneta (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the effectiveness of the contradictory delimitation principle in enhancing legal certainty and the quality of land administration public services at the Gorontalo City Land Office. The research employed a qualitative descriptive method with a case study approach through in-depth interviews, participatory observation, and document analysis. The findings reveal that the implementation of the contradictory delimitation principle is relatively effective in promoting transparency, accountability, and boundary certainty, though its application remains suboptimal. Supporting factors include clear regulations, the commitment of civil servants, and community participation through the PTSL program. In contrast, inhibiting factors involve limited human resources, low public participation, and technical measurement challenges. The principle’s implementation has led to an 18% decrease in land disputes over the past two years and improved public trust in land services. These findings indicate that the contradictory delimitation principle serves not only as an administrative mechanism but also as a participatory and preventive instrument in achieving transparent, equitable, and sustainable land governance.